Strategy Management of Waterboom Bali Tourism Object In The New Normal Tourism Era - Roels Ni Made Sri Puspa Dewi (Jurnal Hospitality dan Pariwisata, 2022)
The Pandemic COVID-19 has had a huge impact on the tourism industry. Waterboom Bali tourist attraction as one of the largest water recreation facilities in Bali has also not escaped the impact of the pandemic. In order to continue to operate and maintain the sustainability of tourism objects, they must be able to live in peace with the Covid-19 virus. This study aims to determine the application of health protocols and tourism management strategies in the new normal era of tourism. Methods of data collection are done by observation, interviews, literature study, and documentation. The sampling technique used was Accidental Sampling. The data analysis method uses data triangulation, namely the triangulation method. The results of this study are that the implementation of the CHSE health protocol has been very good for tourists and workers. Implementation of health protocols in the form of check-in for eligibility to enter tourist destinations on the PeduliLindungi application, checking body temperature, using complete personal protective equipment, and Sanitation Team for periodic environmental cleaning. The management strategy in the new normal of tourism is in the form of promoting ticket prices according to tourist classifications and operating schedules only on weekends.